Łacińskie podstawy kultury europejskiej a cywilizacja chrześcijańska Polski i jej Kresów Wschodnich = The Latin foundations of European culture and the Christian civilisation of Poland and its eastern borderlands - Partacz, Czesław (1952- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Polish state was established over a thousand years ago on the foundation of the Christian culture of the Roman Empire and is currently the last bastion of Christianity in a modern secularised Europe. An important role in the development of historic Catholic Poland was played by the "Kresy", or Eastern borderlands, which were formed following the Union of Lublin in 1569.
Keywords: Poland`s eastern borderlands; Kresy; Christianity; high culture; the Polish-Lithuanian Commonwealth; the Union of Lublin; Soviet and Ukrainian persecution of Polishness; outstanding figures from the "Kresy"; Kresy Wschodnie; Kultura wysocka; chrześcijaństwo; Rzeczpospolita Obojga Narodów; Unia Lubelska; prześladowania